Community Political Participation In The 2019 Presidential And Vice-Presidential Elections In Malang Regency - Catur WIdo Haruni (Audito Comparative Law Journal (ACLJ), 2022)
Elections are a form of the will of the people in a democracy, without any election a country that calls its country a democracy must not be a democracy in the truest sense.  Democracy cannot live alone without the participation of the people.  Democracy is a superstructure that must be sustained by the substructure, that is, the people.  It is within this framework that society can play a role as a subject in determining the future direction of the nation and its state. In the 2019 Presidential and Vice-Presidential Elections, the level of participation of the people of Malang Regency is quite high and the high factor of the level of political participation of the people of Malang Regency is inseparable from the role and function of the KPU, the Po Party litik, Civil Society and the media are going well to make the 2019 elections a success.